Political communication - Seib, Philip M., 1949-; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
'Political Communication' provides an overview of the broad landscape of political communication, with material suited for the theorist and the more practically inclined.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Communication in politics; Electronic books